The impact of sustainability practices on financial performance: Empirical evidence from Sweden - Pham Duc Cuong; Thi Ngoc Anh Do; Doan Thanh Nga; Nguyen Thi Xuan Hong; Thi Kim Yen Pham (Cogent Business & Management, 2021)
This study aims at empirically exploring the influence of sustainability practices on the finan cial performance of 116 listed Swedish companies in the year 2019. The research findings indicate a positive relationship between corporate sustainability and financial performance that is measured by earnings yield, return on asset, return on equity and return on capital employed. However, when it comes to a market-based financial measure, Tobin's Q, the result is inconclusive. Finally, to improve financial performance, firms are recommended to e ngaging in Dow Jones Sustainability Index, prepare their sustainability report in accordance with Global Reporting Initiative (GRI) Standards, improve their sustainable growth rate, as well as keep a high position in the corporate social responsibility ranking.
Keywords: G18; G30; G32; 650; sustainability; sustainable development; green initiatives; financial performance